Curriculum Design and Classroom Management
DOI: 10.4018/978-1-4666-8246-7.ch046
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Problem-Based Learning with Flipped Classroom on Elementary Students' Computing Skills

Abstract: This study investigated, via quasi-experiments, the effects of problem-based learning with flipped classroom (FPBL) on the development of students' learning performance. In this study, 144 elementary school students were selected from six grade sections taking a course titled ‘Production of Ebook', and were assigned into the following three groups: FPBL group (n = 50), PBL group (n = 48), Control group (n = 46). The authors collected both quantitative and qualitative data, including interviews with students an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
2

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 10 publications
3
29
0
2
Order By: Relevance
“…This study showed that the new flipped classroom instructional approach can help students perform significantly better overall than students in traditional classrooms, supporting the results of previous studies (Bhagat et al, 2016;Chao et al, 2015;Schultz et al, 2014;Tsai et al, 2015).…”
Section: Student Learning Gainssupporting
confidence: 80%
See 2 more Smart Citations
“…This study showed that the new flipped classroom instructional approach can help students perform significantly better overall than students in traditional classrooms, supporting the results of previous studies (Bhagat et al, 2016;Chao et al, 2015;Schultz et al, 2014;Tsai et al, 2015).…”
Section: Student Learning Gainssupporting
confidence: 80%
“…Then, most class time is spent on group learning activities that are focusing on applying the knowledge learned from the video lectures, such as solving advanced problems with the support of the teacher and peers or working on projects. Additional in-class activities include but are not limited to individual practices, student presentations, and taking quizzes.Even though after-class activity is not common in the flipped classroom model, the review of the literature shows that some teachers practice completion of self-evaluation or reflection as an after-class activity (Bhagat, Chang & Chang, 2016;Clark, 2015;Lai & Hwang, 2016;Mazur, Brown & Jacobsen, 2015;Schultz, Duffield, Rasmussen & Wageman, 2014;Wang, 2016).The benefits of the flipped teaching method in the current literature are listed as follows:(1) students move at their own pace, (2) doing 'homework' in class gives teachers better insight into student difficulties and learning styles, (3) teachers can more easily customize and update the curriculum and provide it to students 24/7, (4) classroom time can be used more effectively and creatively, (5) teachers using the method report seeing increased levels of student achievement, interest, and engagement, (6) learning theory supports the new approaches, and (7) the use of technology is flexible and appropriate for 21st century learning (Chao, Chen & Chuang, 2015;Chen, 2016;Fulton, 2012;Snyder, Paska & Besozzi, 2014;Tsai, Shen & Lu, 2015). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of applying FCA are varied. Some studies found that FCA improves learners' academic achievements (Bhagat, Chang, & Chang, ; Chao, Chen, & Chuang, ; Huang & Hong, ; Schultz, Duffield, Rasmussen, & Wageman, ; Tsai, Shen, & Lu, ), whereas other studies demonstrated no improvement (Chen, Wang, Li, Bao, & Ren, ; Clark, ; DeSantis, Van Curen, Putsch, & Metzger, ; Kirvan, Rakes, & Zamora, ). This discrepancy in the results of the studies seems reasonable to justify the current study but, at the same time, points to the importance of using a new approach based on theoretical frameworks that can justify this difference.…”
Section: Introductionmentioning
confidence: 99%
“…Lu (2011) analysed Taiwanese junior high school students' Chinese performance on the Basic Competence Test for Junior High School Students and found that the average score of the classical Chinese examination was Lawrence and Sankey (2013) Adoption of the flipped classroom strategy into nursing education (Lawrence andSankey, 2013) Goh and Adoption of the flipped classroom strategy with open-course contents to provide learners with learning scaffold (Goh andSankey, 2013) Huang (2013) Adoption of the flipped classroom strategy into Chinese with interactive mobile Apps (Huang, 2013). Tsai, Shen, Lu (2015) Comparison the learning effectiveness between flipped classroom strategy and other teaching methods (Tsa, Shen, & Lu, 2015) Fardoun & Alghazzaw (2014 Adoption of the interactive learning system with facilitating flipped classroom strategy Chen, Worden, & Bradley (2015) Adoption of the flipped classroom strategy into medical education (Chen, Worden, &Bradley, 2015) Chao, Chen andChuang (2015) Adoption of the flipped classroom strategy for engineering learning in senior high school Wang (2015) Adoption of the game-based interactive response system with flipped classroom strategy lower than that of the modern Chinese examination. Tang (2011) indicated that students rely heavily on Chinese teachers' sentence by sentence explanation, and hence, they lack opportunities to achieve active thinking, thus resulting in poor classical Chinese learning performance.…”
Section: Classical Chinese Learning and Teachingmentioning
confidence: 99%